Hubungan Antara Tingkat Pengetahuan Ibu Tentang Imunisasi Dengan Kelengkapan Imunisasi Pada Bayi Usia 0-14 Bulan di Kelurahan Talaka Kab. Ma’rang - Nurdalifah Nurdalifah (Universitas Muhamadiyah Manado, 2021)
The Infant Mortality Rate (IMR) in Indonesia in 2007 was 34 per 1000 live births, decreased in 2012 to 32 per 1000 live births. One of the causes of Infant Mortality Rate (IMR) is incomplete basic immunization. The role of parents, especially maternal knowledge, is one of the factors in achieving complete basic immunization coverage rates. The aim of this research is to determine the relationship between the level of maternal knowledge about immunization and the completeness of immunization in babies aged 0-14 months in Talaka Village, Kab. Ma'rang, using analytical observation methods with a cross sectional approach. The population of this study were mothers who had babies aged 0-14 months and . The sample was selected using a simple purpose sampling technique with a sample size of 62 respondents, data collection using a questionnaire. Data analysis used univariate analysis and bivariate analysis using the chi squere test. The results of the analysis show that there is a relationship between the mother's level of knowledge about immunization and the completeness of immunization in babies aged 0-14 months In Talaka Village, Kab. Ma'rang with p value = 0.002.